2023
DOI: 10.1002/advs.202302298
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ZBED6 Protects Against Sepsis‐Induced Muscle Atrophy by Upregulating DOCK3‐Mediated RAC1/PI3K/AKT Signaling Pathway in Pigs

Abstract: Sepsis‐induced muscle atrophy often increases morbidity and mortality in intensive care unit (ICU) patients, yet neither therapeutic target nor optimal animal model is available for this disease. Here, by modifying the surgical strategy of cecal ligation and puncture (CLP), a novel sepsis pig model is created that for the first time recapitulates the whole course of sepsis in humans. With this model and sepsis patients, increased levels of the transcription factor zinc finger BED‐type containing 6 (ZBED6) in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
0
0
0
Order By: Relevance
“…Adipogenesis necessitates the coordinated interaction of multiple cell type functions. ScRNA-seq has been extensively employed to investigate adipose tissue heterogeneity and adipogenic-lineage cells identification. ,, Given the potential of porcine fat in tissue engineering , and as a medical model, , we integrated data from mouse and human studies for a comprehensive single-cell analysis. Our results suggested that porcine and human adipose tissues perform similar functions, further supporting the use of pigs as valuable animal models in human adipose research.…”
Section: Discussionmentioning
confidence: 99%
“…Adipogenesis necessitates the coordinated interaction of multiple cell type functions. ScRNA-seq has been extensively employed to investigate adipose tissue heterogeneity and adipogenic-lineage cells identification. ,, Given the potential of porcine fat in tissue engineering , and as a medical model, , we integrated data from mouse and human studies for a comprehensive single-cell analysis. Our results suggested that porcine and human adipose tissues perform similar functions, further supporting the use of pigs as valuable animal models in human adipose research.…”
Section: Discussionmentioning
confidence: 99%
“…Our high-throughput data suggest a signaling output tied to Unc80-mediated neuronal regulation, potentially involved in neuronal differentiation or electrophysiological alterations, signifying cellular changes at the molecular level. One particular gene, Zebd6, shows a significant change in expression in our dataset and is known to play a role in metabolism and signal transduction pathways [ 61 , 62 , 63 ]. However, its specific functions in the olfactory system and the associated signaling cascades remain undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, scRNA‐seq has been applied to explore heterogeneity in human and mice skeletal muscle. Porcine muscle (also referred to as pork) provides an important source of dietary protein for humans, and pigs have been widely used as models for various human conditions and diseases, including diseases related to xenotransplantation and muscle atrophy induced by sepsis, due to the similarities in organ size and physiology 7,8 . Here, muscle tissues of longissimus dorsi (LD, majorly composed of fast‐twitch myofibres) and soleus (SOL, contained more slow‐twitch myofibre compared with other parts) from 3‐day‐old piglets were subjected to 10× scRNA‐seq.…”
Section: Introductionmentioning
confidence: 99%
“…Porcine muscle (also referred to as pork) provides an important source of dietary protein for humans, and pigs have been widely used as models for various human conditions and diseases, including diseases related to xenotransplantation and muscle atrophy induced by sepsis, due to the similarities in organ size and physiology. 7 , 8 Here, muscle tissues of longissimus dorsi (LD, majorly composed of fast‐twitch myofibres) and soleus (SOL, contained more slow‐twitch myofibre compared with other parts) from 3‐day‐old piglets were subjected to 10× scRNA‐seq. Our work explores the heterogeneity of myogenic cells and reveals a novel interaction between MuSCs and FAPs mediated by FGF7–FGFR2, and exogenous FGF7 facilitates proliferation of myogenic SCs and thus benefits muscle regeneration and counteracts age‐related myopathy.…”
Section: Introductionmentioning
confidence: 99%